Facile synthesis of Bi2WO6/rGO nanocomposites for photocatalytic and solar cell applications. Issue 11 (1st June 2021) - Shad, Naveed Akhtar; Sajid, Muhammad Munir; Afzal, Amir Muhammad; Amin, Nasir; Javed, Yasir; Hassan, Safia; Imran, Zahid; Razaq, Aamir; Yousaf, Muhammad Imran; Munawar, Anam; Sharma, Surender Kumar
Abstract: Manipulation of materials at nanoscale provides many new and enhanced properties to be utilized for multifaceted applications, which was not possible before. In this study, we fabricated Bi2 WO6 /rGO composites using hydrothermal method. The obtained composites were then examined using different analytical techniques such as XRD, SEM, TEM, FTIR, XPS, BET, and AFM. Their catalytic properties were assayed by carrying out the degradation of organic dye Rhodamine B (RhB) and employed as a hole transport layer (HTL) in the perovskite solar cells. The fabricated nanocomposites were able to degrade 98% of dye solution within 4 h. The improved photocatalysis is attributed to a large surface area 86.06 m 2 /g with pore size 7.812 nm and enhanced separation of electron-hole pair charges due to rGO sheets. The open-circuit voltage was increased up to 0.94 V when composite materials were used as HTL. The power conversion efficiency (PCE) of the device was enhanced to 11% because of the improvement in the interface quality between HTL and the perovskite layer. It is conceived that the fabricated nanomaterial may show excellent potential in smart solar cell applications.